Influence of cognitive load on the dynamics of neurophysiological adjustments during fatiguing exercise. (7th February 2019) - Chatain, Cyril; Radel, Rémi; Vercruyssen, Fabrice; Rabahi, Tahar; Vallier, Jean‐Marc; Bernard, Thierry; Gruet, Mathieu
Abstract: We aimed to determine the neurophysiological mechanisms associated with reduced endurance performance during cognitive‐motor dual task at different levels of cognitive load, compared to a motor task alone. Eighteen healthy men performed isometric quadriceps contractions at 15% of maximal voluntary contraction (blocks of 170 s interspaced by neuromuscular evaluations) until exhaustion. This task was performed on three separate days: (a) in the absence of concomitant cognitive task, (b) with concomitant 1‐back task, and (c) with concomitant 2‐back task. Autonomic nervous system activity, perceived exertion, and cognitive performance were continuously monitored. Peripheral and central determinants of neuromuscular function were assessed at rest, between each block, and at task failure using femoral nerve stimulation. Endurance time was shorter during 2‐back (982 ± 545 s) and 1‐back (1, 128 ± 592 s) conditions, compared with control (1, 306 ± 836 s). Voluntary activation level was lower in 2‐back (87.1%; p  < 0.001) and 1‐back (88.6%; p  = 0.04) conditions compared to control (91.2%) at isotime (100% of the shortest test duration). Sympathetic activity showed a greater increase in 2‐back condition compared to control. Perceived muscular exertion was higher during 2‐back than during control. Cognitive performance decreased similarly with time during both cognitive‐motor dual task but was always lower during 2‐back condition. Motor performance is reduced when adding a concomitant demanding memory task to a prolonged isometric exercise. This can be explained by the interaction of various psychological and neurophysiological factors including higher perceived exertion, greater perturbations of autonomic nervous system activity, and cerebral impairments leading to earlier onset of central fatigue. Abstract : We demonstrated that the decline in endurance performance when adding a complex cognitive task to a prolonged motor task is caused by interaction of various neurophysiological and psychological factors. They may include higher perceived exertion related to the concomitant development of mental fatigue, greater perturbations of autonomic nervous system activity, and adjustments at the brain level causing an earlier onset of central fatigue. These findings, shedding new light on the mechanisms underlying reduced performance during prolonged cognitive‐motor dual task, will help promote the development of new interventions to counteract fatigue, particularly in real‐life situations characterized by cognitively demanding motor tasks.